2022
DOI: 10.1097/cce.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Angiotensin II for Catecholamine Refractory Septic or Distributive Shock on Mortality: A Propensity Score Weighted Analysis of Real-World Experience in the Medical ICU

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Although treating patients in shock with Ang-2 makes sense pathophysiologically, the study by Quan et al and Bellomo et al showed that patients in shock treated with Ang-2 had higher mortality rate. 3,46 However, in the same study, the mortality rate was significantly lower when Ang-2 is given to patients with elevated renin. 3,46 In vasodilatory shock, renin production is triggered to increase Ang-2 and induce vasoconstriction, but in these patients the mechanism failed.…”
Section: Dovepressmentioning
confidence: 78%
See 4 more Smart Citations
“…Although treating patients in shock with Ang-2 makes sense pathophysiologically, the study by Quan et al and Bellomo et al showed that patients in shock treated with Ang-2 had higher mortality rate. 3,46 However, in the same study, the mortality rate was significantly lower when Ang-2 is given to patients with elevated renin. 3,46 In vasodilatory shock, renin production is triggered to increase Ang-2 and induce vasoconstriction, but in these patients the mechanism failed.…”
Section: Dovepressmentioning
confidence: 78%
“…3,46 However, in the same study, the mortality rate was significantly lower when Ang-2 is given to patients with elevated renin. 3,46 In vasodilatory shock, renin production is triggered to increase Ang-2 and induce vasoconstriction, but in these patients the mechanism failed. 3 The study by Bellomo et al showed that there was an increase in the levels of Ang-1 and Ang-1/Ang-2 ratio in patients with vasodilatory shock compared to controls, while the levels of Ang-2 in both groups tended to remain.…”
Section: Dovepressmentioning
confidence: 78%
See 3 more Smart Citations